Pembuatan Kompos Menggunakan Tumbler di Desa Karanggatak Kabupaten Boyolali - Melda Rizki Indriani Siregar; Ratih Kemala Dewi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Compost is an organic material that is very useful for plant growth. Agricultural waste can mostly be used as compost. Making compost using a tumbler is a way to introduce appropriate technology (TTG) to the community simply and easily in accordance with the needs desired by farmers and rural communities. The purpose of the composting program is to introduce and make simple compost to support sustainable agriculture by utilizing agricultural waste. The program will be held on July 17 until August 9, 2019 in Karanggatak Village, Boyolali Regency. Data collection during the program was carried out by conducting direct observations through community observation and interviews in the utilization of agricultural waste in the form of cow dung, water hyacinth, hay, leaf litter and grass as compost material. Utilizing compost with a tumbler as a composting tool can be widely used in every household to be used in making organic compost. Composted material is easily obtained waste. Compost is made in aerobic conditions. The process of reversing / stirring the compost using a tumbler is easier to do and does not cause dirty. The size and location of the tumbler can be easily adjusted. Keywords : agricultural waste, organic matter, sustainable agriculture, yard